124k views
0 votes
Simplify (5x - 10) - (3x + 8)

User Loonatick
by
4.9k points

2 Answers

3 votes

Answer:

2(x-9)

Explanation:

open the brackets by multillying - sign with the entries of the second bracket

5x-10-3x-8

adding like term variables

2x-18

taking common

2(x-9)

User Chankruze
by
4.7k points
2 votes

Answer:

2x-18 is the answer.

Explanation:

=(5x-10)-(3x+8)

Opening the brackets to simplify

=5x-10-3x-8

Combining the like terms

=5x-3x-10-8

=2x-18

Hope it will help you ^_^

User Hobenkr
by
5.1k points